PENGARUH PEMBERIAN PUPUK UREA DAN PUPUK KANDANG KAMBING TERHADAP BEBERAPA SIFAT KIMIA TANAH DAN HASIL TANAMAN SAWI HIJAU - Hilwa Walida; Fitra Syawal Harahap; Badrul Ainy Dalimunthe; Rosmidah Hasibuan; Ade Parlaungan Nasution; Simon Haholongan Sidabukke (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
This study was aimed to elucidate the effect of the application of urea fertilizer and goat manure on some soil chemical properties and yield of green mustard plant (Bressicca juncea L). This study was conducted with a randomized block design consisting of two factors. The first factor was the application of goat manure (K) consisting of three levels, i.e. (K1) 1 t goat manure ha-1, (K2) 1.5 t goat manure ha-1, and (K3) 2 t goat manure ha-1. The second factor was the application of urea fertilizer consisting of two dose levels, i.e. (U1 75 kg) urea fertilizer ha-1, and (U2) 100 kg urea fertilizer ha-1. The measured parameters were soil organic-C content, soil total N content, and fresh weight of the green mustard plant. Results of the study showed that the combination of 2 t goat manure ha-1 and 100 kg urea fertilizer ha-1 was the best treatment that significantly affected soil organic-C content, soil total N, soil C/N ratio, and yield of fresh weight of the mustard green plant.